The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/crat.201500014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of carbon and silicon carbide contamination during the melting process of the Czochralski silicon crystal growth

Abstract: Carbon contamination in single crystalline silicon is detrimental to the minority carrier lifetime, one of the critical parameters for electronic wafers. In order to study the generation and accumulation of carbon contamination, transient global modeling of heat and mass transport was performed for the melting process of the Czochralski silicon crystal growth. Carbon contamination, caused by the presence of carbon monoxide in argon gas and silicon carbide in the silicon feedstock, was predicted by the fully co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…They reported the results by suing a quasi-static meth calculation. Such a method cannot take into account C accumulation during CZ-Si c growth [6], then the quasi-static assumption is not able to predict the C content in Si Then, the transient method of heat and mass transport is necessary to study C cond tion quantitatively during the melting process of CZ-Si crystal growth [15].…”
Section: Czochralski Methodsmentioning
confidence: 99%
“…They reported the results by suing a quasi-static meth calculation. Such a method cannot take into account C accumulation during CZ-Si c growth [6], then the quasi-static assumption is not able to predict the C content in Si Then, the transient method of heat and mass transport is necessary to study C cond tion quantitatively during the melting process of CZ-Si crystal growth [15].…”
Section: Czochralski Methodsmentioning
confidence: 99%
“…Reactions ( 4)-( 6) are involved at the gas/Si interface and in the unmelted Si feedstock. To investigate the surface reaction and deposition, a simplified model for SiC generation by the reaction between CO and Si was used for the surface of the packed Si chunks 17) . O, C, SiO, CO, and SiC coexist in the unmelted Si feedstock and at the gas/Si interface.…”
Section: Reactions and Deposition On The Surface Of Si Chunksmentioning
confidence: 99%
“…Transport phenomena of C as well as relevant impurities and species in the CZ-Si process have been extensively studied in the last few decades [9][10][11][12][13][14][15][16][17] . It has been found that back diffusion of the generated CO is the main origin of C contamination in Si feedstock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al. recently addressed the generation, transport, and accumulation of C during the melting process in a CZ‐Si furnace. The accumulation of C in the melt was investigated according to the transient feature of the CZ‐Si process.…”
Section: Introductionmentioning
confidence: 99%